The effect of the epidemic of Neodiprion sertifer (Geoffroy, 1785) (Hymenoptera: Diprionidae) on diameter increment in Brutian pine - Zeynep Eda Akıncı; Mustafa Avcı; Şükran Oğuzoğlu (Turkish Journal of Forestry, 2022)
Neodiprion sertifer (Geoffroy, 1785) (Hymenoptera: Diprionidae) is an important pine insect that is distributed naturally in Asian and European continents and as an invasive species in North America. In this study, the effects of the outbreak caused by pine sawfly on the diameter increment of trees in 2005 in Sarıköy brutian pine (Pinus brutia Ten.) forests situated in the province of Afyonkarahisar, district of Başmakçı were determined. The annual ring widths for 2000-2014 were evaluated in the increment cores taken from the trees that were damaged and not damaged by insects. Diameter increment was found to decrease by 42.7% in trees that were damaged by the insects and by 20.8% in the trees that were not damaged in 2005 compared to 2004. While a decrease of 7.1% persisted in the damaged trees in 2006 compared to 2005, while there was an increase of 9.7% in the undamaged trees. The damaged trees had an increase of 53.8% in 2007 compared to 2006 while a decline of 25.5% was found in the undamaged trees. A statistically significant difference was found in the mean annual ring widths of the damaged trees between 2004 and 2005 when the damage occurred and the following year, 2006 (p<0,05). The effects of precipitation and drought on the diameter increase in the trees damaged by the insect were investigated in 2005 and 2006. It was concluded that the decline in the diameter increment of the trees was related to the insects whereas precipitation and drought did not have any impact.